2017
DOI: 10.1186/s40738-017-0034-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors among women with self-reported infertility

Abstract: BackgroundAmongst women with certain types of ovulatory disorder infertility, the studies are conflicting whether there is an increased risk of long-term cardiovascular disease risk. This paper evaluates the associations of several CVD risk factors among Framingham women with self-reported infertility.MethodsWomen who completed the Framingham Heart Study Third Generation and Omni Cohort 2 Exam 2 (2008–2011), and reported on past history of infertility and current cardiovascular disease status were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 52 publications
3
45
3
2
Order By: Relevance
“…A 2017 cross-sectional analysis involving women who completed the Framingham Heart Study Third Generation and Omni Cohort 2 Exam 2 (2008-2011) and reported infertility showed that selfreported infertility was associated with CVD risk factors such as elevated body mass index and waist circumference. 27 However, an analysis of data from the Women's Health Initiative Observational Study did not find a history of infertility to be associated with coronary heart disease. 28 A 2016 observational study involving women receiving infertility therapy found that failure of therapy was associated with 19% higher annual rates of cardiovascular events.…”
Section: Does Reproductive Therapy Increase Women's Risk Of Ischemic mentioning
confidence: 98%
“…A 2017 cross-sectional analysis involving women who completed the Framingham Heart Study Third Generation and Omni Cohort 2 Exam 2 (2008-2011) and reported infertility showed that selfreported infertility was associated with CVD risk factors such as elevated body mass index and waist circumference. 27 However, an analysis of data from the Women's Health Initiative Observational Study did not find a history of infertility to be associated with coronary heart disease. 28 A 2016 observational study involving women receiving infertility therapy found that failure of therapy was associated with 19% higher annual rates of cardiovascular events.…”
Section: Does Reproductive Therapy Increase Women's Risk Of Ischemic mentioning
confidence: 98%
“…Though initially thought to be expressed only by the kidneys and then secreted into the blood, further research proved its expression in the reproductive systems, especially female, with it being found in oocytes, granulosa, and interstitial and luteal cells of the ovary, suggesting its possibly critical role in reproduction and hormonal regulation (Zhou et al, ). Mechanisms by which Renalase could influence female fertility could be through the cardiovascular and endocrine effect of catecholamines (Bitar, ; Crist & Hulka, ), as several studies have shown how cardiovascular risk and disease are associated with female infertility (Dickey, Taylor, Rye, Lu, & Sartor, ; Mahalingaiah et al, ; Verit, Yildiz Zeyrek, Zebitay, & Akyol, ). Moreover, catecholamines also have demonstrable effects on the hypothalamic–pituitary–ovarian axis (Schenker, Meirow, & Schenker, ) and could thus affect fertility in females.…”
Section: Introductionmentioning
confidence: 99%
“…The SNP rs2576178 is associated with HTN (Buraczynska, Zukowski, Buraczynska, Mozul, & Ksiazek, ), stroke (Zhang et al, ) and coronary heart disease (Li et al, ), while rs10887800 is associated with stroke (Buraczynska et al, ). Given the expression of Renalase in female reproductive tissues, as well as the less‐explored association of cardiovascular risk and disease with female infertility (Dickey et al, ; Mahalingaiah et al, ; Verit et al, ), we decided to explore the association of SNPs rs2576178 and rs19887800 with female infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Исследования показывают, что неспособность к зачатию связана с сердечно-сосудистым риском, поскольку у многих нефертильных женщин имеются кардиометаболические нарушения, которые потенциально повышают риск развития сердечнососудистой патологии [3,12]. В дополнение к этому некоторые виды бесплодия ассоциируются с повышенным риском развития сердечно-сосудистых заболеваний [7,8,10,11].…”
unclassified